Faktor - Faktor yang berhubungan dengan Preeklampsia pada Ibu Hamil Trimester III - Andira; Sri Rahayu (Jurnal Sains & Kesehatan, 2023)
Preeclampsia is hypertension that occurs in pregnant women at 20 weeks of gestation or after delivery which is marked by an increase in blood pressure to 140/90 mmHg. The aim of this research is determine the factors associated with preeclampsia in third trimester pregnant women in the dahlia room at the Public Hospital. Sample: The sample of this study were third trimester pregnant women with preeclampsia as many 124 people.This type of research uses quantitative analytic methods with a cross-sectional approach. Results: there is a significant relationship between preeclampsia, gestational age, parity, history of hypertension and family history of pregnant women with the results of the chi-square test statistical test obtained p-value <0.05.